Research on a lunar mobile spiral surface-soil sampler. (July 2020) - Hou, Xuyan; Guo, Hongwei; Cao, Pan; Xue, Pingping; Tang, Tianfeng; Deng, Zongquan
This article presents the design of a spiral sampling device to perform lunar soil sampling and packaging, considering the special lunar environment and the physical and mechanical properties of the lunar soil. Combining the mechanical properties of lunar soil and the geometrical characteristics of the sampling device, the contact model between particles and the contact parameters between device and particles were adjusted. Through a discrete element simulation of the sampling process, the particles' streamline, which is between the screw conveying modules and the sampling bailer, is derived. This result provides a theoretical foundation for the structural optimization of the device. Finally, a sampling experiment in simulated lunar soil verifies the feasibility of the sampling device.